Use and influence of web analytics in news production: a case study of a peruvian digital media - Barrenechea Arango, Melissa (2021)
The digital age has added a key element in news production: Web analytics, which allows understanding the audience through a series of indicators and metrics. The purpose of this research is to describe the use and influence of Web analytics in news production by publishers and editors of the RPP Noticias website, the main Peruvian radio station. Based on twelve in-depth interviews, the perceptions and experiences of journalists regarding this audience measurement tool are recorded. The research confirmed that Web analytics has a level of influence on the content selected by editors and on the location of the news on the website cover page. Furthermore, this finding suggests that publishers present mixed views: those dealing with hard topics (politics, public administration, international issues) defend their own journalistic criteria, while those who deal with soft topics (celebrities, sports and entertainment) point to a balance between their judgment and their audience’s preferences.